Persistent SARS-CoV-2 RNA Shedding Without Evidence of Infectiousness: A Cohort Study of Individuals With COVID-19. (27th February 2021) - Owusu, Daniel; Pomeroy, Mary A; Lewis, Nathaniel M; Wadhwa, Ashutosh; Yousaf, Anna R; Whitaker, Brett; Dietrich, Elizabeth; Hall, Aron J; Chu, Victoria; Thornburg, Natalie; Christensen, Kimberly; Kiphibane, Tair; et al.
Abstract: Background: To better understand severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) shedding and infectivity, we estimated SARS-CoV-2 RNA shedding duration, described participant characteristics associated with the first negative rRT-PCR test (resolution), and determined if replication-competent viruses was recoverable ≥10 days after symptom onset. Methods: We collected serial nasopharyngeal specimens from 109 individuals with rRT-PCR–confirmed COVID-19 in Utah and Wisconsin. We calculated viral RNA shedding resolution probability using the Kaplan-Meier estimator and evaluated characteristics associated with shedding resolution using Cox proportional hazards regression. We attempted viral culture for 35 rRT-PCR–positive nasopharyngeal specimens collected ≥10 days after symptom onset. Results: The likelihood of viral RNA shedding resolution at 10 days after symptom onset was approximately 3%. Time to shedding resolution was shorter among participants aged <18 years (adjusted hazards ratio [aHR], 3.01; 95% confidence interval [CI], 1.6–5.6) and longer among those aged ≥50 years (aHR, 0.50; 95% CI, .3–.9) compared to participants aged 18–49 years. No replication-competent viruses were recovered. Conclusions: Although most patients were positive for SARS-CoV-2 for ≥10 days after symptom onset, our findings suggest that individuals with mild to moderate COVID-19 are unlikely to be infectious ≥10 days after symptom onset. Abstract : The majority of participants with mild to moderate COVID-19 continued to shed SARS-CoV-2 from the nasopharynx ≥10 days after symptom onset. However, we did not recover any replication-competent virus from 35 rRT-PCR–positive nasopharyngeal specimens collected ≥10 days after symptom onset.